AÇÃO ANTIMICROBIANA DE Anacardium Occidentale L: potencial biotecnológico na geração de produtos anticárie - SILVA, Rubenice Amaral da (2012)
Anacardium occidentale, family Anacardiaceae, is popularly known as cashew tree and it is widely used as food and medicine. This study aimed to review data on antimicrobial properties of Anacardium occidentale, to evaluate the antioxidant and antimicrobial action and to investigate the chemical composition of the extracts of flowers (EBFL), leaves (EBFO) and stem bark (EBC) of A. occidentale, to evaluate the antimicrobial activity of the byproduct obtained in order to use it in the prophylaxis and adjunctive treatment of caries. This review considered publications by Medline, Lilacs, Scielo, Chemical Abstracts, PubMed, Biological Abstract, Web of Sciences and Highwire, between 1980 and 2011, using the descriptors: Anacardium occidentale, antimicrobial, antibacterial, antifungal and pharmacological activity and cashew. The antioxidant activity was determined by DPPH assay and the antimicrobial activity by agar diffusion, broth dilution, determination of the minimum bactericidal concentration (MBC) or minimum fungicide concentration (MFC), using standard strains of Streptococcus mutans, Lactobacillus acidophilus, Staphylococcus aureus, MRSA, Enterococcus faecalis, Streptococcus pyogenes, Pseudomonas aeruginosa, Proteus mirabilis, Escherichia coli, Klebsiella pneumoniae, Helicobacter pylori and Candida albicans and clinical samples of Salmonella choleraesuis, Candida albicans and Candida tropicalis. The chemical composition was determined by colorimetry, chromatography and spectroscopy. The EBFL, more active, was fractionated and the fractions were also evaluated for antibacterial action. Regarding the literature review, 44 articles and 3 dissertations about antimicrobial properties of cashew tree were found. Bark extracts were the mostly used in those researches (30%). Staphylococcus aureus, including MRSA strains were the most studied microorganisms (68%). All extracts have showed antioxidant activity compared to quercetin. On the other hand, the result of experimental protocols showed that the EBFL was presented as the one with the most active antimicrobial action against all microorganisms evaluated either in planktonic cultures or the biofilm. The fraction F1 and bioproduct-based EBFL have also showed potent antimicrobial activity. In EBFL there were identified organic acids, alkaloids, phenolics, hydrolysable tannins, flavones, flavonols, xanthines, steroids and triterpenes. This is the first research on the antioxidant and antimicrobial properties of the flowers of A. occidentale on the prophylactic and therapeutic use in oral diseases, particularly caries and candidiasis, activities that may be related to the presence of flavonoids, tannins, organic acids, alkaloids and phenolic compounds such as anacardic acid, cardol and cardanol.